The Relationship Between Interpersonal Trust and Job Satisfaction at Employees Of Company: Hubungan antara Interpersonal Trust dengan Kepuasan Kerja pada Karyawan Perusahaan - Afif Muzaqi; Effy Wardati Maryam (Academia Open, 2022)
This research was conducted because there are still phenomena of employees who have a low level of satisfaction. This study aims to determine the relationship between interpersonal trust and job satisfaction at employees of PT. Garuda Mas Citra Cemerlang.. This research includes correlational quantitative research. The population in this study were 60 employees, all of which became the research sample. The sampling technique in this study was saturated sampling. The data collection technique in this study used 2 psychological scales, namely the interpersonal trust scale consisting of 40 items and the job satisfaction scale consisting of 50 items. The results of data analysis showed a correlation coefficient of 0.302, a significance of 0.000 <0.05, so the hypothesis was accepted. The result of the determination coefficient test is 0.351 (Adjusted R Square) which shows that the interpersonal trust variable contributes 35.1% to job satisfaction. Highlights: Low employee satisfaction: This research addresses the issue of low job satisfaction among employees at PT. Garuda Mas Citra Cemerlang. Interpersonal trust and job satisfaction: The study explores the relationship between interpersonal trust and job satisfaction among the employees. Significant contribution: The findings reveal that interpersonal trust contributes 35.1% to job satisfaction, highlighting the importance of trust in the workplace. Keywords: Interpersonal trust, job satisfaction, employees, PT. Garuda Mas Citra Cemerlang, quantitative research